Recent advances of organometallic complexes in emerging photovoltaics. Issue 6 (9th September 2021) - Gao, Huaizhi; Yu, Runnan; Ma, Zongwen; Gong, Yongshuai; Zhao, Biao; Lv, Qianglong; Tan, Zhan'ao
Abstract: Organometallic complexes (OMCs) consisting of organic and metal active moieties have shown immense potential for application in solar cells. The diverse structure, rich porosity, and unique charge centers of OMCs enable them to be functional in solar cells. In this review, we introduced four types of OMCs, such as crown organometallic complexes, β ‐diketone metal complexes, cyclometallic complexes, and main chain metal‐containing polymers, providing an in‐depth analysis of the structure‐performance relationship. OMCs could serve as active or interlayer materials in a variety of solar cell systems such as organic solar cells, perovskite solar cells, and dye‐sensitized solar cells, especially some metals to improve the photoelectric performance of the device as dopants. In the end, perspectives on the opportunities and challenges of OMCs are given. Abstract :